PsycEXTRA Dataset 2006
DOI: 10.1037/e513092010-001
|View full text |Cite
|
Sign up to set email alerts
|

Service Academy 2006 Gender Relations Survey

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of Information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
5
3
0
Order By: Relevance
“…Though we cannot compare the incidence rates directly to those reported in U.S. studies-because of differences in time frames (see note 7), the pattern of experiences reported by participants in our study are remarkably similar to those reported in studies of women in the U.S. military (Culbertson & Rosenfeld, 1993, 1996Fitzgerald et al, 1999;Rosen & Martin, 1998). For example, Lipari and her colleagues have found that sexist behaviors, crude or offensive behaviors, and unwanted sexual attention occur more frequently than sexually coercive behaviors (Lipari & Lancaster, 2003;Lipari et al, 2005Lipari et al, , 2006. Perhaps what is more interesting about these results is that women appear to experience patterns of harassing experiences rather than distinct, isolated episodes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Though we cannot compare the incidence rates directly to those reported in U.S. studies-because of differences in time frames (see note 7), the pattern of experiences reported by participants in our study are remarkably similar to those reported in studies of women in the U.S. military (Culbertson & Rosenfeld, 1993, 1996Fitzgerald et al, 1999;Rosen & Martin, 1998). For example, Lipari and her colleagues have found that sexist behaviors, crude or offensive behaviors, and unwanted sexual attention occur more frequently than sexually coercive behaviors (Lipari & Lancaster, 2003;Lipari et al, 2005Lipari et al, , 2006. Perhaps what is more interesting about these results is that women appear to experience patterns of harassing experiences rather than distinct, isolated episodes.…”
Section: Discussionsupporting
confidence: 86%
“…Lipari et al (2003) found that among women surveyed in 2002, 50% experienced sexist behaviors, 45% crude or offensive behaviors, 27% experienced unwanted sexual attention, and 8% experienced sexually coercive behaviors in the previous 12 months. Similar results are reported in studies of reserve component personnel and cadets and midshipmen at U.S. service academies (Lipari et al, 2005(Lipari et al, , 2006.…”
Section: Incidence and Dimensions Of Sexual Harassment Of Women In Thsupporting
confidence: 89%
See 1 more Smart Citation
“…Some reports excluded sexual assault data (e.g., Thomas, Newell, & Eliassen, 1995), whereas others emphasized associated behaviors (e.g., stalking; Lipari et al, 2006). As another illustration, current DoD interpretation of annual reporting requirements under Public Law 109-364 indicates that detailed surveys and focus groups will be conducted only biannually (DoD, 2009a).…”
Section: Examining Reported Rates Of Men's Mstmentioning
confidence: 94%
“…Weighted sample surveys during this period show reported incidence rates between 0.9 and 2.0 (Lipari, Cook, Rock, & Matos, 2008;Lipari & Lancaster, 2003;Lipari, Lancaster, & Jones, 2005;Rock & Lipari, 2009). Martindale (1990 Yearly social climate surveys from the military service academies suggest a stable reported rate between 1% and 2% over the past decade (Cook, Jones, Lipari, & Lancaster, 2005;Cook & Lipari, 2008;DoD, 2007b;Department of the Air Force, 2003;Lipari et al, 2006; Office of the Inspector General of the Department of Defense [OIG], 2005). Universal screening for MST among men in the VA shows similar reported rates of 1.1% to 1.2% (Kimerling et al, 2007(Kimerling et al, , 2008.…”
Section: Abstract Military Veterans Sexual Trauma Posttraumatic Stmentioning
confidence: 97%